2021
DOI: 10.1007/s10147-021-02033-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of axicabtagene ciloleucel in Japanese patients with relapsed or refractory large B-cell lymphoma

Abstract: Background Axicabtagene ciloleucel (axi-cel) is an autologous chimeric antigen receptor T-cell based anti-CD19 therapy. The ZUMA-1 study, multicenter, single-arm, registrational Phase 1/2 study of axi-cel demonstrated high objective response rate in patients with relapsed/refractory large B-cell lymphoma. Here, we present the results of the bridging study to evaluate the efficacy and safety of axi-cel in Japanese patients (JapicCTI-183914). Methods This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Part of the lesions in the mediastinum was adjacent to the right side of the pericardium ( Figure 1 ). The patient was referred to our hospital for anti-CD19 CAR-T cell therapy with axicabtagene ciloleucel as part of a phase 2 clinical trial (JapicCTI-183914; https://rctportal.niph.go.jp/en/detail?trial_id=JapicCTI-183914 ) ( 6 ). He had a history of a duodenal ulcer but not cardiovascular disease.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Part of the lesions in the mediastinum was adjacent to the right side of the pericardium ( Figure 1 ). The patient was referred to our hospital for anti-CD19 CAR-T cell therapy with axicabtagene ciloleucel as part of a phase 2 clinical trial (JapicCTI-183914; https://rctportal.niph.go.jp/en/detail?trial_id=JapicCTI-183914 ) ( 6 ). He had a history of a duodenal ulcer but not cardiovascular disease.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Three second-generation anti-CD19 CAR T-cell therapies have demonstrated efficacy and safety in Japan for patients with R/R aggressive B-cell NHL: tisagenlecleucel, 10 axicabtagene ciloleucel, 9 and, with this report, liso-cel. Other CAR T-cell therapies did not permit enrollment of patients with secondary CNS lymphoma in their respective pivotal trials, but independent, retrospective, investigator-led studies have demonstrated that these patients can be successfully treated with CAR T-cell therapy.…”
Section: Discussionmentioning
confidence: 65%
“…The Japanese subgroup analysis of tisagenlecleucel reported an ORR of 78%, grade 3 or 4 CRS per the Penn grading system in two of nine patients (22%), and grade 3 NEs in one of nine patients (11%) 10 . In a study of axicabtagene ciloleucel in Japanese patients reporting an ORR of 87%, grade 4 CRS per the Lee 2014 criteria occurred in one patient (6%); no NEs were reported 9 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations